The neural signature of high myopia: structural and functional brain alterations and their cognitive-emotional associations - Li, Xuan; Zhao, Kuan; Deng, Boling; Wu, Zhengzheng; Wei, Ling (Frontiers in Cell and Developmental Biology, 2025)
Beyond refractive error, myopia is increasingly recognized as a systemic condition with neurological implications, associated with visual dysfunction and structural retinal–choroidal alterations. This review synthesizes neuroimaging evidence demonstrating widespread neuroanatomical and functional brain changes in myopia, including cortical thinning, white matter disorganization, and disrupted functional connectivity, which may be associated with changes in cognitive-emotional systems rather than just the visual system. Mechanistically, these neural signatures reflect experience-dependent neural plasticity, dopaminergic dysregulation in the retinal ON pathway, and non-image-forming disruptions mediated by intrinsically photosensitive retinal ganglion cells, compounded by vascular dysfunction and impaired neurovascular coupling. Clinically, these findings highlight the importance of early neurocognitive risk assessment through multimodal imaging and psychological screening. By elucidating the retina–brain axis, this review bridges ophthalmological and neurological perspectives, guiding precision interventions for comprehensive, life-course myopia management.